Resin composition having excellent recyclability and multilayer structure using the same

By adding acid modified PO to the resin composition and adjusting its component ratio and density, the problem of adhering to the screw and die during a long-term melt forming process is solved, and the impact resistance and melt forming properties are improved at low temperatures.

CN114746500BActive Publication Date: 2025-04-01KURARAY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080085649.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-12
Filing Date
2020-12-11
Publication Date
2025-04-01
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

Prior Art During the long-term continuous melt forming process, the resin composition is prone to adhere to the screw and die head, resulting in accumulation of deteriorated substances, affecting the impact resistance and appearance of the molded product, and performs poorly at low temperatures.

Method used

The resin composition containing polyolefin (PO), ethylene-vinyl alcohol copolymer (EVOH) and acid-modified PO is used to increase the glass transition temperature and acid value of the resin by adjusting the proportion and density of each component to enhance its melt forming properties and low-temperature impact resistance.

Benefits of technology

The amount of deteriorated substance attached to the screw and die head during the long-term continuous melt forming process of the resin composition is achieved, and a molded product with excellent impact resistance is obtained at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005091112280000201
    Figure GDA0005091112280000201
Patent Text Reader

Abstract

A resin composition comprising, relative to 100 parts by mass of a polyolefin (A), 0.1 to 20 parts by mass of an ethylene-vinyl alcohol copolymer (B), 0.1 to 20 parts by mass of an acid-modified polyolefin (C), and 0.1 to 10 parts by mass of an acid-modified polyolefin (D), wherein the ethylene unit content of (B) is 15 to 60 mol%, the saponification degree is 85 mol% or more, and the density of (A) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 , the density of (C) is 0.89g / cm 3 Above and less than 0.97g / cm 3 , the density of (D) is 0.85g / cm 3 Above and less than 0.89g / cm 3 , and the glass transition temperature measured by dynamic viscoelasticity measurement is below ‑30°C. The resin composition has good melt moldability, and even when melt molding is continuously performed for a long time, the amount of deteriorated products attached to the screw and the die head is small. In addition, by using the resin composition, a molded product with excellent impact resistance at low temperature can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition containing a polyolefin and an ethylene-vinyl alcohol copolymer, a method for producing the same, and a multilayer structure, a molded product, and a fuel container using the resin composition. In addition, the present invention relates to a recycling aid used in the production of the multilayer structure using the resin composition. Background Art

[0002] At present, for a multilayer structure including a polyolefin (hereinafter sometimes abbreviated as "PO") layer and an ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as "EVOH") layer having excellent barrier properties, its barrier properties are effectively utilized for various purposes such as food packaging containers and fuel containers. Such a multilayer structure is used as various molded products such as films, sheets, cups, trays, bottles, etc. At this time, the ends and defective products generated when obtaining the above-mentioned various molded products are sometimes recovered, melt-molded, and reused as at least one layer of the multilayer structure including the PO layer and the EVOH layer. Such a recycling technology is useful in terms of waste reduction and economy, and is widely adopted.

[0003] However, when the recyclate of the multilayer structure including the PO layer and the EVOH layer is reused, gelation occurs due to thermal degradation during melt molding, or the degraded product adheres to the extruder, making it difficult to perform long-term continuous melt molding. In addition, since such degraded products are mixed into the molded product, there is also a problem of poor appearance. Furthermore, the multilayer structure having a resin composition layer including such recyclate also has insufficient impact resistance.

[0004] In order to solve such a problem, for example, Patent Document 1 discloses a mixed resin comprising PO, a saponified ethylene-vinyl acetate copolymer, and an acid-modified olefin-carboxylic acid vinyl ester copolymer, wherein the olefin content of the acid-modified olefin-carboxylic acid vinyl ester copolymer is 50 to 95 mol%, and the difference between the ethylene content of the saponified ethylene-vinyl acetate copolymer and the olefin content of the acid-modified olefin-carboxylic acid vinyl ester copolymer is in the range of 20 to 70 mol%. It is disclosed that the mixed resin can provide a molded product with less fisheyes, streaks, or striations even in long-term continuous melt molding with less screw adhesion of deteriorated products.

[0005] Patent Document 2 describes a resin composition comprising PO, EVOH and two kinds of acid-modified PO, wherein the melt flow rate (MFR) of the PO at 190°C and 2.16 kg load is 0.01 to 10 g / 10 minutes, the acid value of one kind of acid-modified PO is 0.1 to 9 mgKOH / g, the acid value of the other kind of acid-modified PO is greater than 10 mgKOH / g and less than 120 mgKOH / g, and the ratio of the MFR (at 190°C and 2.16 kg load) of the acid-modified PO with a higher acid value to the MFR (at 190°C and 2.16 kg load) of the PO (acid-modified PO / PO) is 50 or more. It is described that the resin composition has a small amount of deteriorated products attached to the screw and the die even when melt-molded continuously for a long period of time, and a molded product excellent in impact resistance and appearance can be obtained.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2012 / 060371

[0009] Patent document 2: International Publication No. 2019 / 021996. Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, when the mixed resin described in Patent Document 1 is subjected to continuous melt molding for a long time, there are still cases where deteriorated products adhere to the screw and the die head, which becomes a problem, and there are cases where the impact resistance of the resulting molded product at low temperatures (e.g., -40°C) is insufficient. In addition, for the resin composition described in Patent Document 2, there are cases where the impact resistance at low temperatures is still insufficient. In this regard, for example, for fuel containers mounted in automobiles, etc., in order to ensure safety, high impact strength is required under a wide temperature range. When a resin composition containing PO and EVOH is used in such a fuel container, in particular, the impact strength at low temperatures becomes a very important factor. In addition, in order to improve the impact resistance at low temperatures, when the composition of the resin composition, the addition of additives, etc. are tested, there are cases where the melt moldability is reduced.

[0012] The present invention is an invention made to solve the above-mentioned problems, and its purpose is to provide a resin composition containing PO and an ethylene-vinyl alcohol copolymer, which has good melt moldability, has a small amount of deteriorated products attached to the screw and the die even when melt molding is continuously performed for a long time, and can obtain a molded product with excellent impact resistance at low temperatures. In addition, the purpose is to provide a method for producing the resin composition, a multilayer structure and a molded product using the resin composition, and a recycling aid suitable for use in the production of the resin composition.

[0013] Solutions to Solve Problems

[0014] The above purpose is achieved by providing the following solution:

[0015] [1] A resin composition comprising 0.1 to 20 parts by mass of an ethylene-vinyl alcohol copolymer (B) (hereinafter sometimes abbreviated as "EVOH (B)"), 0.1 to 20 parts by mass of an acid-modified polyolefin (C) (hereinafter sometimes abbreviated as "acid-modified PO (C)"), and 0.1 to 10 parts by mass of an acid-modified polyolefin (D) (hereinafter sometimes abbreviated as "acid-modified PO (D)"), relative to 100 parts by mass of a polyolefin (A) (hereinafter sometimes abbreviated as "PO (A)"), wherein the EVOH (B) has an ethylene unit content of 15 to 60 mol% and a saponification degree of 85 mol% or more, and the density of PO (A) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 The density of acid-modified PO(C) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 The density of acid-modified PO (D) is 0.85 g / cm 3 Above and less than 0.89g / cm 3 , the glass transition temperature measured by dynamic viscoelasticity measurement is below -30°C;

[0016] [2] The resin composition according to [1], wherein the acid value of the acid-modified PO (D) is 3 mgKOH / g or more and less than 100 mgKOH / g;

[0017] [3] The resin composition according to [1] or [2], wherein the acid-modified PO (C) comprises an acid-modified polyolefin (C1) having an acid value of 0.1 mgKOH / g or more and less than 10 mgKOH / g (hereinafter sometimes abbreviated as “acid-modified PO (C1)”) and an acid-modified polyolefin (C2) having an acid value of 10 mgKOH / g or more and less than 100 mgKOH / g (hereinafter sometimes abbreviated as “acid-modified PO (C2)”);

[0018] [4] The method for producing a resin composition according to [3], comprising: a step of melt-kneading a recyclate of a multilayer structure comprising a PO (A) layer, an EVOH (B) layer and an acid-modified PO (C1) layer, and a recycling aid comprising an acid-modified PO (C2) and an acid-modified PO (D);

[0019] [5] A multilayer structure comprising a layer containing the resin composition described in any one of [1] to [3] as a main component;

[0020] [6] The multilayer structure according to [5], further comprising a PO (A) layer, an EVOH (B) layer, and an acid-modified PO (C1) layer;

[0021] [7] A molded article using the multilayer structure described in [5] or [6];

[0022] [8] A fuel container using the multilayer structure described in [5] or [6].

[0023] [9] A recovery aid, wherein the recovery aid comprises an acid-modified PO (D), wherein the density of the acid-modified PO (D) is 0.85 g / cm 3 Above and less than 0.89g / cm 3 , and the glass transition temperature measured by dynamic viscoelasticity measurement is -30°C or less;

[0024]

[10] The recycling aid according to [9], wherein the acid value of the acid-modified PO (D) is 3 mgKOH / g or more and less than 100 mgKOH / g;

[0025]

[11] The recovery aid according to [9] or

[10] , further comprising a 3 Above and less than 0.97g / cm 3 , an acid-modified PO (C2) having an acid value of 10 mgKOH / g or more and less than 100 mgKOH / g, and a mass ratio (C2 / D) of the acid-modified PO (C2) to the acid-modified PO (D) of 10 / 90 to 90 / 10;

[0026]

[12] The recovery aid according to any one of [9] to

[11] , further comprising a recovery aid having a density of 0.89 g / cm 3 Above and less than 0.97g / cm 3 PO(A), the mass ratio (A / D) of PO(A) to acid-modified PO(D) is 10 / 90 to 90 / 10.

[0027] Effects of the Invention

[0028] According to the present invention, a resin composition containing PO and EVOH can be provided, which has good melt moldability, and the amount of degraded products attached to the screw and the die is small even when melt molding is performed continuously for a long time, and a molded product with excellent impact resistance at low temperature can be obtained. In addition, a method for manufacturing the resin composition, a multilayer structure and a molded product using the resin composition, and a recycling aid suitable for use in the manufacture of the resin composition can be provided. In the present invention, sometimes the property of the amount of degraded products attached to the screw and the die is small even when melt molding is performed continuously for a long time is expressed as "recyclability". DETAILED DESCRIPTION

[0029] The resin composition of the present invention contains 0.1 to 20 parts by mass of EVOH (B), 0.1 to 20 parts by mass of acid-modified PO (C), and 0.1 to 10 parts by mass of acid-modified PO (D) relative to 100 parts by mass of PO (A), wherein the ethylene unit content of EVOH (B) is 15 to 60 mol%, the saponification degree is 85 mol% or more, and the density of PO (A) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 The density of acid-modified PO(C) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 The density of acid-modified PO (D) is 0.85 g / cm 3 Above and less than 0.89g / cm 3 , and the glass transition temperature measured by dynamic viscoelasticity measurement is -30°C or less. In particular, by including the acid-modified PO (D) having a low density and a low glass transition temperature, the impact resistance of the resin composition at low temperatures tends to be improved.

[0030] (PO(A))

[0031] The resin composition of the present invention contains PO(A). The density of PO(A) is 0.89 g / cm 3 Above, preferably 0.94 g / cm 3 The density of PO(A) is less than 0.89g / cm 3 When the heat resistance and solvent resistance are reduced. In addition, the density of PO (A) is less than 0.97g / cm 3 , preferably 0.96 g / cm 3 The density of PO(A) is 0.97 g / cm 3 When it is greater than this, the impact resistance at low temperature decreases.

[0032] Examples of PO(A) include polypropylene; propylene-based copolymers of propylene and α-olefins such as ethylene, 1-butene, 1-hexene, and 4-methyl-1-pentene; polyethylenes such as low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, and high-density polyethylene; ethylene-based copolymers of ethylene and α-olefins such as 1-butene, 1-hexene, and 4-methyl-1-pentene; poly(1-butene), poly(4-methyl-1-pentene), and the like. PO(A) may be used alone or in combination of two or more. Among them, from the viewpoint of obtaining a molded product having further excellent solvent resistance and impact resistance at low temperatures, PO(A) is preferably polyethylene, and more preferably high-density polyethylene.

[0033] The MFR of PO(A) at 190°C and 2.16 kg load measured by the method described in JIS K 7210:2014 is preferably 0.01 g / 10 min or more. When the MFR of PO(A) is 0.01 g / 10 min or more, the viscosity difference with EVOH(B) becomes small, and good melt moldability tends to be obtained. In addition, the MFR of PO(A) is preferably 10 g / 10 min or less, and more preferably 5 g / 10 min or less. When the MFR of PO(A) is 10 g / 10 min or less, the viscosity difference with EVOH(B) becomes small, and good melt moldability tends to be obtained.

[0034] (EVOH(B))

[0035] The ethylene unit content of EVOH (B) is 15 to 60 mol%, and the saponification degree is 85 mol% or more. EVOH (B) can be obtained by saponifying an ethylene-vinyl ester copolymer. As the vinyl ester, a substance represented by vinyl acetate can be cited, and other fatty acid vinyl esters (vinyl propionate, vinyl pivalate, etc.) can also be used.

[0036] The ethylene unit content of EVOH (B) is preferably 20 mol% or more, more preferably 23 mol% or more. In addition, the ethylene unit content of EVOH (B) is preferably 55 mol% or less, more preferably 50 mol% or less. When the ethylene unit content of EVOH (B) is less than 15 mol%, when the resin composition of the present invention is melt-molded for a long time, the amount of resin attached to the screw increases. In addition, when the ethylene unit content exceeds 60 mol%, for example, when a multilayer structure containing EVOH (B) is recycled and reused to manufacture the resin composition of the present invention, the barrier properties of the multilayer structure serving as the raw material are reduced.

[0037] The saponification degree of the vinyl ester unit of EVOH (B) is preferably 90 mol% or more, more preferably 98 mol% or more, further preferably 99 mol% or more, and may be 100 mol%. When the saponification degree of EVOH (B) is less than 85 mol%, the recyclability deteriorates. The ethylene unit content and saponification degree of EVOH (B) can be obtained by nuclear magnetic resonance (NMR) method.

[0038] EVOH (B) may have units derived from other monomers other than ethylene, vinyl esters and saponified products thereof. When EVOH (B) has the aforementioned other monomer units, the content of the aforementioned other monomer units relative to all structural units of EVOH (B) is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, and particularly preferably 5 mol% or less. In addition, when EVOH (B) has units derived from the aforementioned other monomers, the content thereof is preferably 0.05 mol% or more, more preferably 0.10 mol% or more. Examples of the other monomers include olefins such as propylene, butene, pentene, and hexene; 3-acyloxy-1-propylene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, 5,6-diacyloxy-1-hexene; , 1,3-diacetoxy-2-methylenepropane and other olefins having an ester group or their saponification products; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid or their anhydrides, salts, or monoalkyl esters or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, methyl allyl sulfonic acid or their salts; vinyl silane compounds such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxy-ethoxy) silane, γ-methacryloxypropyl methoxysilane; alkyl vinyl ethers, vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinylidene chloride, etc.

[0039] EVOH (B) can be post-modified by methods such as urethanization, acetalization, cyanoethylation, and oxyalkyleneization.

[0040] The MFR of EVOH (B) measured at 190°C and 2.16 kg load according to JIS K 7210: 2014 is preferably 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more. In addition, the MFR of EVOH (B) is preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, and further preferably 30 g / 10 min or less. When the MFR of EVOH (B) is within the above range, the recyclability of the resin composition of the present invention tends to be good.

[0041] The content of EVOH (B) in the resin composition of the present invention is 0.1 parts by mass or more, preferably 1 part by mass or more, relative to 100 parts by mass of PO (A). When the content of EVOH (B) is less than 0.1 parts by mass, when the resin composition of the present invention is melt-formed for a long time, it is difficult to cause the problem of recyclability, and the advantage of adopting the present invention is small. In addition, the content of EVOH (B) is 20 parts by mass or less, preferably 15 parts by mass or less, relative to 100 parts by mass of PO (A). When the content of EVOH (B) exceeds 20 parts by mass, the melt-formability of the resin composition of the present invention is reduced, and when the resin composition of the present invention is melt-formed for a long time, the recyclability is deteriorated, and the impact resistance of the obtained molded product at low temperature is reduced. EVOH (B) can be used alone or in combination of two or more.

[0042] (Acid-modified PO(C))

[0043] The resin composition of the present invention tends to have better recyclability by containing acid-modified PO (C). The density of the acid-modified PO (C) is 0.89 g / cm 3 Above, preferably 0.91 g / cm 3 The density of acid-modified PO(C) is less than 0.89 g / cm 3 When the heat resistance and solvent resistance are reduced. In addition, the density of acid-modified PO (C) is less than 0.97 g / cm 3 , preferably 0.94 g / cm 3 The density of acid-modified PO (C) is 0.97 g / cm 3 When it is greater than this, the impact resistance at low temperature decreases.

[0044] As the acid-modified PO (C), there can be mentioned graft-modified PO obtained by graft-modifying PO with an acid, and olefin-based copolymers obtained by copolymerizing an olefin and an acid. Among them, graft-modified PO is suitable as the acid-modified PO (C). From the viewpoint of excellent compatibility with PO (A), the acid-modified PO (C) is preferably a substance obtained by acid-modifying the same type of PO as PO (A). For example, when PO (A) is polypropylene, the acid-modified PO (C) is preferably acid-modified polypropylene, and when PO (A) is polyethylene, the acid-modified PO (C) is preferably acid-modified polyethylene.

[0045] As the graft-modified PO used as the acid-modified PO (C), there can be mentioned those obtained by graft-modifying the PO or the like exemplified as the substance used as the PO (A) with an acid. As the acid for grafting the PO, an unsaturated carboxylic acid or its derivative can be used, for example, acrylic acid, methacrylic acid, fumaric acid, itaconic acid, maleic acid; maleic anhydride, itaconic anhydride, etc. Among them, maleic anhydride-grafted PO is most suitable.

[0046] Examples of the olefin copolymer used as the acid-modified PO (C) include copolymers obtained by further containing an acid as a copolymerization component in addition to the PO listed as the PO (A). Examples of the acid used in this case include the acids mentioned above as the acids for grafting PO.

[0047] From the viewpoint of recyclability, the acid value of the acid-modified PO (C) is preferably 0.1 mgKOH / g or more and less than 100 mgKOH / g. The acid value of PO (C) is more preferably 3 mgKOH / g or more, and further preferably 18 mgKOH / g or more. In addition, the acid value of PO (C) is more preferably 70 mgKOH / g or less, and further preferably 50 mgKOH / g or less. When the acid value of PO (C) is 0.1 mgKOH / g or more, the dispersibility of EVOH (B) in the resin composition becomes good, and the resulting molded product tends to have improved impact resistance at low temperatures. When the acid value of PO (C) is less than 100 mgKOH / g, the melt moldability tends to become good.

[0048] From the viewpoint of recyclability, it is preferred that the acid-modified PO (C) comprises an acid-modified PO (C1) having an acid value of 0.1 mgKOH / g or more and less than 10 mgKOH / g and an acid-modified PO (C2) having an acid value of 10 mgKOH / g or more and less than 100 mgKOH / g. The acid value of the acid-modified PO (C1) is 0.1 mgKOH / g or more, preferably 0.5 mgKOH / g or more, more preferably 0.7 mgKOH / g or more, and further preferably 1 mgKOH / g or more. When the acid value of the acid-modified PO (C1) is 0.1 mgKOH / g or more, there is a tendency that the recyclability becomes good. In addition, the acid value of the acid-modified PO (C1) is less than 10 mgKOH / g, preferably 5 mgKOH / g or less, and more preferably 3 mgKOH / g or less. When the acid value of the acid-modified PO (C1) is less than 10 mgKOH / g, there is a tendency that the melt formability becomes good. The acid value of the acid-modified PO (C2) is 10 mgKOH / g or more, preferably 12 mgKOH / g or more, more preferably 18 mgKOH / g or more, and further preferably 30 mgKOH / g or more. When the acid value of the acid-modified PO (C2) is 10 mgKOH / g or more, the recyclability tends to be good. In addition, the acid value of the acid-modified PO (C2) is less than 100 mgKOH / g, preferably 80 mgKOH / g or less, more preferably 60 mgKOH / g or less, and further preferably 50 mgKOH / g or less. When the acid value of the acid-modified PO (C2) is less than 100 mgKOH / g, the melt-formability tends to be good.

[0049] Since the acid-modified PO (C1) has suitable adhesion to PO (A) and EVOH (B), it is suitable for use as an adhesive layer of the multilayer structure used as a raw material, for example, when the multilayer structure is used as a raw material of the resin composition of the present invention described later. When PO (C1) is used as the adhesive layer of the multilayer structure, when the acid value of PO (C1) is 0.1 mgKOH / g or more, there is a tendency that PO (A) and EVOH (B) have excellent adhesion. On the other hand, when the aforementioned acid value is less than 10 mgKOH / g, the following tendency is formed: the viscosity matching of the resin constituting the multilayer structure becomes good, and the layer thickness of the obtained multilayer structure becomes constant. Usually, when the recycled material of such a multilayer structure is used to manufacture the resin composition of the present invention, the acid-modified PO (C1) is contained in the resin composition of the present invention. By including the acid-modified PO (C1) in the resin composition of the present invention, there is a tendency that the dispersibility of EVOH (B) is improved and the impact resistance of the obtained molded product at low temperature is improved.

[0050] The resin composition of the present invention contains acid-modified PO (C2), which tends to improve recycling performance. Acid-modified PO (C2) has a high acid value, so when the resin composition of the present invention contains acid-modified PO (C2), it is preferably added as a recycling aid.

[0051] The acid-modified PO (C) may be used alone or in combination of two or more.

[0052] The content of the acid-modified PO (C) in the resin composition of the present invention is 0.1 parts by mass or more relative to 100 parts by mass of PO (A), preferably 0.5 parts by mass or more, and more preferably 2 parts by mass or more. When the content of the acid-modified PO (C) is less than 0.1 parts by mass, the recyclability is reduced. In addition, the content of the acid-modified PO (C) is 20 parts by mass or less, preferably 15 parts by mass or less, and more preferably 10 parts by mass or less. When the content of the acid-modified PO (C) exceeds 20 parts by mass, the melt moldability of the resin composition of the present invention is reduced, and the recyclability of the resulting molded product is reduced.

[0053] The mass ratio (C2 / C1) of the acid-modified PO (C1) to the acid-modified PO (C2) in the resin composition of the present invention is preferably 0.1 / 99.9 to 50 / 50. When the mass ratio (C2 / C1) is within the above range, the recyclability tends to be better.

[0054] (Acid-modified PO(D))

[0055] The resin composition of the present invention tends to have improved impact resistance at low temperatures by containing acid-modified PO (D). The density of the acid-modified PO (D) is 0.85 g / cm 3 Above, preferably 0.86 g / cm 3 The density of acid-modified PO (D) is less than 0.85 g / cm 3 In addition, the density of acid-modified PO (D) is less than 0.89 g / cm 3 , preferably 0.88 g / cm 3 The density of acid-modified PO (D) is 0.89 g / cm 3 When it is greater than this, the impact resistance at low temperature decreases.

[0056] The glass transition temperature of the acid-modified PO (D) is -30°C or lower, preferably -40°C or lower, and more preferably -45°C or lower. When the glass transition temperature of the acid-modified PO (D) exceeds -30°C, the impact resistance of the obtained molded product at low temperature decreases. The glass transition temperature of the acid-modified PO (D) may be -70°C or higher. The glass transition temperature of the acid-modified PO (D) can be measured by a dynamic viscoelasticity measurement method, specifically, it can be measured by the method described in the Examples.

[0057] Examples of the acid-modified PO (D) include graft-modified PO obtained by graft-modifying PO with an acid and acid-modified olefin-based copolymers obtained by copolymerizing an olefin and an acid. Among them, graft-modified PO is suitable as the acid-modified PO (D).

[0058] As graft-modified PO used as acid-modified PO (D), for example, a material obtained by graft-modifying the same type of PO as the material exemplified as the material used as PO (A) above with an acid, etc., among which preferred are graft-modified copolymers of propylene and α-olefins such as ethylene, 1-butene, 1-hexene, and 4-methyl-1-pentene; ethylene-based copolymers of ethylene and α-olefins such as 1-butene, 1-hexene, and 4-methyl-1-pentene. As the acid for grafting PO, an unsaturated carboxylic acid or its derivative can be used, and for example, acrylic acid, methacrylic acid, fumaric acid, itaconic acid, maleic acid; maleic anhydride, itaconic anhydride, etc. can be mentioned. Among them, maleic anhydride graft-modified PO is most suitable.

[0059] As the olefin copolymer used as the acid-modified PO (D), there can be mentioned a copolymer obtained by further containing an acid as a copolymerization component to the same type of PO as the above-mentioned substance used as PO (A). As the acid used in this case, there can be mentioned the acids exemplified as the acids for grafting PO mentioned above.

[0060] The acid value of the acid-modified PO (D) is preferably 3 mgKOH / g or more, more preferably 10 mgKOH / g or more, and further preferably 15 mgKOH / g or more. When the acid value of the acid-modified PO (D) is 3 mgKOH / g or more, the impact strength at low temperatures tends to be improved. In addition, the acid value of the acid-modified PO (D) is preferably less than 100 mgKOH / g, more preferably 70 mgKOH / g or less, and further preferably 50 mgKOH / g or less. When the acid value of the acid-modified PO (D) is less than 100 mgKOH / g, the melt moldability tends to be good. In the case of containing two or more acid-modified PO (D), the weighted average value of each acid value at the mixing mass ratio is set as the acid value of the acid-modified PO (D).

[0061] The content of the acid-modified PO (D) in the resin composition of the present invention is 0.1 parts by mass or more relative to 100 parts by mass of PO (A), preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more. When the content of the acid-modified PO (D) is less than 0.1 parts by mass, the recyclability of the resin composition of the present invention deteriorates, and the impact resistance of the resulting molded product at low temperatures is reduced. In addition, the content of the acid-modified PO (D) is 10 parts by mass or less, preferably 7 parts by mass or less. When the content of the acid-modified PO (D) exceeds 10 parts by mass, due to the excessive reaction of the acid-modified PO (D) with EVOH (B), the melt moldability is reduced, and the proportion of the acid-modified PO (D) increases, thereby reducing the solvent resistance.

[0062] The MFR (190°C, 2.16 kg load) of the acid-modified PO (D) is preferably 0.1 g / 10 min or more. When the MFR of the acid-modified PO (D) is 0.1 g / 10 min or more, the recyclability and impact resistance at low temperatures of the resin composition of the present invention tend to be good. On the other hand, the MFR of the acid-modified PO (D) is preferably 100 g / 10 min or less, more preferably 20 g / 10 min or less. When the MFR is 100 g / 10 min or less, the impact resistance at low temperatures tends to be good. The acid-modified PO (D) may be used alone or in combination of two or more.

[0063] (Other compounds)

[0064] In the resin composition of the present invention, other compounds other than PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D) may also be contained without hindering the effect of the present invention. As examples of the aforementioned other compounds, resins other than PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D), carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts (alkali metal salts, alkaline earth metal salts), antioxidants, ultraviolet light absorbers, plasticizers, lubricants, fillers, antistatic agents can be cited. The content of the aforementioned other compounds in the resin composition of the present invention is usually 50% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, and particularly preferably 3% by mass or less.

[0065] Examples of the resin other than PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D) include polyamide, polyvinyl chloride, polyvinylidene chloride, polyester, polystyrene, epoxy resin, acrylic resin, polyurethane resin and polyester resin.

[0066] The carboxylic acid compound may be a monocarboxylic acid, a polycarboxylic acid, or a combination thereof. The carboxylic acid compound may be an ion, and the carboxylic acid ion may form a salt with a metal ion. The content of the carboxylic acid and the carboxylic acid ion is preferably 1 to 400 ppm. As the carboxylic acid compound, aliphatic carboxylic acids such as acetic acid and stearic acid may be suitably used. When the resin composition of the present invention contains a carboxylic acid compound, a tendency to prevent coloration during melt molding is formed.

[0067] The phosphate compound is not particularly limited, and various acids such as phosphoric acid and phosphorous acid, and their salts, etc. can be used. As a phosphate, it can be contained in any form of dihydrogen phosphate, monohydrogen phosphate, and phosphate, preferably dihydrogen phosphate. Its cationic species are also not particularly limited, and alkali metal salts are preferably used. Among them, sodium dihydrogen phosphate and potassium dihydrogen phosphate are preferred. When the resin composition of the present invention contains a phosphate compound, the content of the phosphate compound is preferably 1 to 500 ppm in terms of phosphate radical conversion. When the content of the phosphate compound is 1 ppm or more, there is a tendency for the coloring resistance during melt molding to become good. On the other hand, when the content of the phosphate compound is 500 ppm or less, there is a tendency for the melt moldability to become good.

[0068] As the boron compound, there is no particular limitation, and examples include boric acids, boric esters, borate salts, boranes, and the like. Specifically, examples of boric acids include orthoboric acid, metaboric acid, tetraboric acid, and the like, examples of boric esters include triethyl borate, trimethyl borate, and the like, and examples of borate salts include alkali metal salts, alkaline earth metal salts, borax, and the like of the various boric acids described above. Among these compounds, orthoboric acid (hereinafter sometimes simply referred to as boric acid) is preferred. When the resin composition of the present invention contains a boron compound, the content of the boron compound is preferably 20 to 2000 ppm in terms of boron element conversion. When the content of the boron compound is 20 ppm or more, a tendency to suppress torque changes during heating and melting is formed. On the other hand, when the content of the boron compound is 2000 ppm or less, there is a tendency to maintain good formability.

[0069] The cationic species of the alkali metal salt is not particularly limited, and is preferably a sodium salt or a potassium salt. The anionic species of the alkali metal salt is also not particularly limited. It can be added as a carboxylate, a carbonate, a bicarbonate, a phosphate, a hydrogen phosphate, a borate, a hydroxide, etc. When the resin composition of the present invention contains an alkali metal salt, the content of the alkali metal salt is preferably 10 to 500 ppm in terms of metal element conversion. When the content of the alkali metal salt is 10 ppm or more, there is a tendency that the interlayer adhesion becomes good. On the other hand, when the content of the alkali metal salt is 500 ppm or less, there is a tendency that the melt stability is excellent.

[0070] The cationic species of the alkaline earth metal salt is not particularly limited, and magnesium salt or calcium salt is suitable. The anionic species of the alkaline earth metal salt is also not particularly limited. It can be added as a carboxylate, carbonate, bicarbonate, phosphate, hydrogen phosphate, borate, hydroxide, etc. The content of the alkaline earth metal salt is preferably 10 to 500 ppm. When the resin composition of the present invention contains an alkaline earth metal salt, it is formed to suppress the deterioration of the molded body when it is repeatedly melt-molded, and to suppress the generation of deteriorated products such as gel.

[0071] Antioxidants: 2,5-di-tert-butylhydroquinone, 2,6-di-tert-butyl-p-cresol, 4,4'-thiobis(6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate, 4,4'-thiobis(6-tert-butylphenol), etc.

[0072] Ultraviolet absorbers: ethylene-2-cyano-3,3'-diphenylacrylate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)5-chlorobenzotriazole, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, etc.

[0073] Plasticizers: dimethyl phthalate, diethyl phthalate, dioctyl phthalate, wax, liquid paraffin, phosphate ester, etc.

[0074] Lubricants: stearamide, oleamide, erucamide, behenamide, ethylene bis stearamide, hydroxymethyl stearamide, N-oleyl palmitamide, N-stearyl erucamide, liquid paraffin, natural paraffin, synthetic paraffin, polyolefin wax, stearyl alcohol, lauryl alcohol, stearic acid, lauric acid, myristic acid, behenic acid, montanic acid, stearyl stearate, stearyl laurate, calcium stearate, magnesium stearate, zinc stearate, lead stearate, etc.

[0075] Fillers: glass fiber, asbestos, balatonite, calcium silicate, etc.

[0076] Antistatic agent: glycerol monofatty acid ester, fatty acid diethanolamide, alkyl diethanolamine, alkyl sulfonate, alkyl benzene sulfonate, alkyl trimethyl ammonium salt, alkyl betaine, alkyl imidazolium betaine, etc.

[0077] Among all the resins in the resin composition of the present invention, the proportion of PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D) is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 98% by mass or more. In addition, the resin constituting the resin composition of the present invention may be substantially only PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D), or may be substantially only PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D). In addition, the proportion of PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D) in the resin composition of the present invention is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, particularly preferably 98% by mass or more, or may be substantially only composed of PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D).

[0078] (Method for producing resin composition)

[0079] The method for producing the resin composition of the present invention is not particularly limited, and examples thereof include a method of dry-mixing PO(A), EVOH(B), acid-modified PO(C) and acid-modified PO(D) and performing melt kneading; a method of melt-kneading a multilayer structure having a PO(A) layer, an EVOH(B) layer and an acid-modified PO(C1) layer and a recovery aid comprising an acid-modified PO(D), etc. In addition, when the resin composition of the present invention contains the aforementioned other compounds, the aforementioned other compounds may be mixed in the above-mentioned dry-mixing process, may be contained in a layer constituting the multilayer structure, may be a layer constituting the multilayer structure, or may be added as a recovery aid during melt kneading. Among them, as a method for producing the resin composition of the present invention, it is preferred to include a method of melt-kneading a multilayer structure having a PO(A) layer, an EVOH(B) layer and an acid-modified PO(C1) layer and a recovery aid comprising an acid-modified PO(D). At this time, it is more preferred that the aforementioned recovery aid also contains an acid-modified polyolefin (C2). From the viewpoint of environment and cost, the multilayer structure used as the raw material of the resin composition is preferably a waste such as burrs generated when producing molded products, or a recycled product such as defective products during molding.

[0080] (Recycling aids)

[0081] The recycling aid of the present invention contains the above-mentioned acid-modified PO (D). By containing the acid-modified PO (D), the recycling property becomes good, and the impact resistance of the molded product obtained after recycling at low temperature tends to become good. The suitable form of the acid-modified PO (D) contained in the recycling aid of the present invention is the same as the PO (D) contained in the aforementioned resin composition. The content of the acid-modified PO (D) in the recycling aid of the present invention is preferably 10% by mass or more, more preferably 25% by mass or more, and further preferably 50% by mass or more. When the recycling aid of the present invention does not contain PO (C2) and PO (A), the PO (D) contained in the recycling aid of the present invention is preferably 80% by mass or more, more preferably 90% by mass or more, and the aforementioned recycling aid may also be substantially composed of only the acid-modified PO (D). The recycling aid of the present invention can be widely used for the recycling of molded products containing PO and EVOH, including the recycling of a multilayer structure containing a PO (A) layer, an EVOH (B) layer and an acid-modified PO (C1) layer.

[0082] From the viewpoint of improving recyclability, it is preferred that the recycling aid of the present invention further comprises acid-modified PO (C2). Suitable forms of the acid-modified PO (C2) used herein are the same as the acid-modified PO (C2) used in the aforementioned resin composition. When the recycling aid of the present invention comprises acid-modified PO (C2), it is preferred that the mass ratio (C2 / D) of the acid-modified PO (C2) relative to the acid-modified PO (D) is 10 / 90 to 90 / 10. When the mass ratio (C2 / D) is within the above range, there is a tendency that the impact resistance and recyclability at low temperatures become further improved. When the recycling aid of the present invention comprises acid-modified PO (D) and acid-modified PO (C2) and does not comprise PO (A), the proportion of acid-modified PO (D) and acid-modified PO (C2) in the recycling aid of the present invention is preferably 90% by mass or more, more preferably 95% by mass or more, and the aforementioned recycling aid may also be substantially composed only of acid-modified PO (D) and acid-modified PO (C2).

[0083] From the viewpoint of recyclability, it is preferred that the recycling aid of the present invention further comprises PO(A). The suitable form of PO(A) used here is the same as the PO(A) used in the aforementioned resin composition. When the recycling aid of the present invention comprises PO(A), the mass ratio (A / D) of PO(A) to acid-modified PO(D) is preferably 10 / 90 to 90 / 10. When the mass ratio (A / D) is within the above range, there is a tendency that the recyclability becomes good. When the recycling aid of the present invention comprises acid-modified PO(D) and PO(A) and does not comprise acid-modified PO(C2), the proportion of PO(A) and acid-modified PO(D) in the recycling aid of the present invention is preferably 90% by mass or more, more preferably 95% by mass or more, and the aforementioned recycling aid may be substantially composed only of PO(A) and acid-modified PO(D). In addition, when the recovery aid of the present invention comprises acid-modified PO (D), PO (A) and acid-modified PO (C2), the proportion of PO (A), acid-modified PO (C2) and acid-modified PO (D) in the recovery aid of the present invention is preferably 90% by mass or more, more preferably 95% by mass or more, and may be substantially composed of PO (A), acid-modified PO (C2) and acid-modified PO (D).

[0084] The recovery aid of the present invention may also include other compounds other than PO (A), acid-modified PO (C2) and acid-modified PO (D) as long as it does not hinder the effect of the present invention. As the aforementioned other compounds, the above-mentioned other compounds that can be included in the resin composition can be cited, and the aforementioned recovery aid may also include EVOH (B) and acid-modified PO (C1). It should be noted that the recovery aid of the present invention can also show high recovery even if it is in the form of not containing metal salts such as alkali metal salts and alkaline earth metal salts. The content of other compounds in the recovery aid of the present invention is usually 50% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, and particularly preferably 3% by mass or less.

[0085] From the viewpoint of compatibility, when the recycling aid of the present invention contains PO(A), it is preferred that the PO(A) contained in the recycling aid and the PO(A) contained in the recycled multilayer structure are the same type of PO. For example, when the PO(A) contained in the recycled multilayer structure is polypropylene, it is preferred that the PO(A) contained in the recycling aid is also polypropylene, and when the PO(A) contained in the recycled multilayer structure is polyethylene, it is preferred that the PO(A) contained in the recycling aid is also polyethylene.

[0086] When the recycling aid of the present invention contains compounds other than the acid-modified PO (D), it is preferred that the acid-modified PO (D) and the compounds other than the acid-modified PO (D) are pre-melted and kneaded to form a recycling aid containing all of these compounds, and then added to the recyclate. Such a recycling aid is suitable for being blended in the recyclate in the form of particles. The recyclate is preferably pre-crushed into an appropriate size, and for the crushed recyclate, a recycling aid in the form of mixed particles is suitable.

[0087] As the raw material of the resin composition of the present invention, only unused resin can be used, but from the viewpoint of reducing the amount of waste and reducing costs, it is preferred to use the recyclate of the above-mentioned multilayer structure as at least a part of the raw material. The raw material of the resin composition of the present invention, the ratio of the aforementioned recyclate is preferably 50% by mass or more. It should be noted that as long as the effect of the present invention is not hindered, as the raw material of the recyclate, the packaging material (multilayer structure) after consumption on the market can also be used. In this case, the packaging material is generally cut, separated and washed as needed, and the process of melt mixing is carried out using an extruder.

[0088] The multilayer structure used as a raw material of the resin composition of the present invention is not particularly limited, and examples thereof include multilayer structures having the following layer configurations. In the following examples, the PO (A) layer is represented as "A", the EVOH (B) layer is represented as "B", the acid-modified PO (C1) layer is represented as "C1", the resin composition layer of the present invention is represented as "E", and direct lamination is represented as " / ".

[0089] 3 layers A / C1 / B, A / B / A5 layers A / C1 / B / C1 / A, A / C1 / B / C1 / E6 layers A / C1 / B / C1 / E / A, E / A / C1 / B / C1 / A, A / E / C1 / B / C1 / E, E / A / C1 / B / C1 / E7 layer A / E / C1 / B / C1 / E / A, A / E / C1 / B / C1 / A / E, E / A / C1 / B / C1 / A / E

[0090] The multilayer structure preferably has the resin composition layer of the present invention from the viewpoint of reducing the amount of waste and cutting costs. In addition, from the viewpoint of improving the adhesion between the layers, it is preferred that the EVOH (B) layer is in contact with the acid-modified PO (C1) layer.

[0091] The overall thickness of the multilayer structure can be appropriately set according to the application. The overall thickness is preferably 50 to 8000 μm. By making the overall thickness 50 μm or more, a multilayer structure with high rigidity can be obtained. An overall thickness of 500 μm or more is more suitable. On the other hand, by making the overall thickness 8000 μm or less, a flexible multilayer structure can be obtained. An overall thickness of 7000 μm or less is more suitable.

[0092] The method for producing the multilayer structure is not particularly limited. For example, molding methods implemented in the field of general PO, such as extrusion molding, blow molding, injection molding, thermoforming, etc., can be cited. Among them, co-extrusion molding and co-injection molding are suitable, and co-extrusion molding is more suitable.

[0093] The multilayer structure of the present invention is excellent in terms of environment and cost by having a layer with the resin composition of the present invention as the main component. Here, "main component" refers to more than 50% by mass, and the proportion of the resin composition of the present invention in the resin composition layer is preferably 70% by mass or more, more preferably 90% by mass or more, and it is further preferred that the resin composition layer is only composed of the resin composition of the present invention. In addition, the multilayer structure of the present invention is preferably a multilayer structure further comprising a PO (A) layer, an EVOH (B) layer and an acid-modified PO (C1) layer. For the suitable layer composition and manufacturing method in the multilayer structure of the present invention, the contents recorded as examples of having a resin composition layer of the present invention in the multilayer structure used as the above-mentioned raw material can be cited. In addition, the multilayer structure of the present invention may have other resin layers other than the PO (A) layer, the EVOH (B) layer and the acid-modified PO (C1) layer without hindering the effect of the present invention. Examples of the other resin layers include ethylene-vinyl acetate copolymer layers, polyester layers such as polyethylene terephthalate, polyester elastomer layers, polyamide layers such as nylon-6 and nylon-66, polystyrene layers, polyvinyl chloride layers, polyvinylidene chloride layers, acrylic resin layers, vinyl ester resin layers, polyurethane layers, and polycarbonate layers.

[0094] A fuel container having a resin composition layer of the present invention is a suitable embodiment of the resin composition of the present invention. Furthermore, a fuel container having a PO (A) layer, an EVOH (B) layer and an acid-modified PO (C1) layer in addition to the resin composition layer of the present invention is a suitable embodiment of the multilayer structure of the present invention. In this case, the fuel container preferably has a PO (A) layer or a resin composition layer of the present invention on the inner and outer layers of the EVOH (B) layer via an acid-modified PO (C1) layer.

[0095] The resin composition of the present invention is excellent in melt formability and recyclability, and the obtained molded product has excellent impact resistance at low temperature, so it can be suitably used in food packaging containers, fuel containers, etc., and is particularly suitable for use as a fuel container. The manufacturing method of the fuel container is not particularly limited, and examples thereof include extrusion molding, blow molding, injection molding, thermoforming, etc. Among them, blow molding and thermoforming are preferred, coextrusion blow molding or coextrusion sheet thermoforming are more preferred, and coextrusion blow molding is further preferred.

[0096] When manufacturing a fuel container by blow molding, any method of co-extrusion blow molding and co-injection blow molding can be used, and co-extrusion blow molding that is easy to correspond to a complex container shape is suitable. In co-extrusion blow molding, a parison is formed by melt extrusion, and the parison is clamped by a pair of blow molding dies, and the parison is sheared (cut) while the facing sheared parts are fused. Then, the sheared parison is expanded in the aforementioned mold to form the shape of the container. However, in the case of a larger size of the container such as a fuel tank for an automobile, the parison is often clamped by a mold and crimped, but shearing is not performed in the mold, and the part overflowing from the surface of the container is cut off at an arbitrary height using a cutting tool or the like.

[0097] In addition, the mold temperature when the fuel container of the present invention is blow-molded is preferably 5 to 30° C., more preferably 10 to 30° C., and even more preferably 10 to 20° C. When the mold temperature is less than 5° C., condensation is likely to form on the mold surface, and the appearance of the molded product may be poor. In addition, when the mold temperature exceeds 30° C., the cooling time of the resin may be prolonged, thereby reducing productivity, and when the resin is not sufficiently cooled, deformation may occur in the molded product.

[0098] The obtained molded product, or a container precursor such as a parison or sheet during molding may be cross-linked by irradiation with radiation or the like.

[0099] When utilizing blow molding to make fuel container, because a large amount of waste material and poorly formed (recyclables) are generated, the waste material and poorly formed containers generated are crushed and reused as a recycling layer (resin composition layer of the present invention) in coextrusion molding, thus, waste material can be reduced, and the effect of environmental protection and cost reduction can be obtained. On the other hand, a variety of components comprising EVOH are mixed in the recycling layer, so it is easy to produce physical properties reduction, as an example thereof, the reduction of impact strength can be cited. When used particularly under an extremely low temperature environment, the fuel container hardens and the impact strength is reduced, thus producing the damage of the box and then producing the risk associated with the major accident of the vehicle. In addition, in recent years, in order to improve the functionality of the fuel container, the ratio of waste material increases, and the thickness of the recycling layer also thickens accordingly. With the increase of the thickness of the recycling layer, the impact strength of the fuel container is reduced, so the impact strength of the recycling layer is required to improve. As mentioned above, the resin composition of the present invention can be made by adding the recovery aid of the present invention in the recycling of waste material, etc. In such a recovery process, the amount of deteriorated products attached to the screw and the die head is small, and the impact resistance of the resulting recycling layer at low temperature is excellent. Therefore, a fuel container having a layer of the resin composition of the present invention formed using recycled materials such as scraps generated during fuel container production and the recycling aid of the present invention has excellent impact resistance at low temperatures.

[0100] The fuel container of the present invention refers to a fuel container mounted on automobiles, motorcycles, ships, airplanes, generators, and industrial and agricultural machines, a portable container for refueling these fuel containers, and a container for storing fuel used to operate them. In addition, as the fuel, conventional gasoline, gasoline blended with methanol, ethanol, toluene, or MTBE, and biodiesel fuel can be cited as representative examples, and other heavy oils, light oils, kerosene, etc. can also be cited.

[0101] Example

[0102] Hereinafter, the present invention will be described in more detail using Examples, but the present invention is not limited to these Examples.

[0103] <Evaluation Method>

[0104] (1)MFR

[0105] The resins used in Examples and Comparative Examples were measured for MFR (g / 10 minutes) using a melt indexer in accordance with JIS K 7210: 2014. The temperature and load varied depending on the type of resin.

[0106] (2) Glass transition temperature

[0107] The glass transition temperature of the resins used in Examples and Comparative Examples was measured by a dynamic viscoelasticity measurement method using RHEOGEL E 4000 manufactured by UBM under the following conditions. The peak temperature of Tan δ was defined as the glass transition temperature.

[0108] Temperature range: -100℃~+40℃

[0109] Heating speed: 3℃ / min (step length 3℃)

[0110] Basic frequency: 11Hz (sine wave)

[0111] Clamp clearance: 20mm

[0112] Test piece dimensions: width 5 mm, thickness 200 μm, length 30 mm.

[0113] (3) Acid value of acid-modified PO

[0114] The acid value of the acid-modified PO used in Examples and Comparative Examples was measured in accordance with JIS K 2501. Xylene was used as a solvent.

[0115] (4) Density

[0116] The density of the resins used in Examples and Comparative Examples was measured using a density gradient tube in accordance with ASTM D 1505.

[0117] (5) Impact strength at -40℃

[0118] The resin composition pellets obtained in the examples and comparative examples were used to produce injection molded products having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm using an injection molding machine (J85AD manufactured by Nippon Steel Works, Ltd.) in accordance with JIS K 7110, and test pieces were obtained by cutting. The IZOD impact strength (kJ / m2) of the obtained test pieces at -40°C was measured using a digital impact tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.). 2 ).

[0119] (6) Evaluation of die head adhesion

[0120] The resin composition pellets obtained in Examples and Comparative Examples were melt-kneaded under the following conditions to continuously produce resin composition pellets, and the amount of resin adhering to the die 15 minutes after the start of production was measured.

[0121] <Extruder conditions>

[0122] Extruder: Single screw extruder ("GT-40-26" manufactured by Plastics Engineering Research Institute, diameter 40 mm, L / D = 26)

[0123] Screw speed: 95rpm

[0124] Discharge: 20kg / hr

[0125] Cylinder and die head temperature settings: C1 / C2 / C3 / C4 / C5 / D=200℃ / 215℃ / 215℃ / 215℃ / 215℃ / 215℃ Plastic extrusion die: 5 holes.

[0126] (7) Evaluation of screw attachment amount

[0127] The resin composition pellets obtained in Examples and Comparative Examples were kneaded using a roll mixer R60 manufactured by Toyo Seiki Seisaku-sho, Ltd. under the following conditions, and the mass of the screw attachment was measured.

[0128] <Mixer conditions>

[0129] Screw speed: 50rpm

[0130] Temperature setting: 215℃

[0131] Duration: 60 minutes

[0132] Atmosphere: Nitrogen.

[0133] (8) Solvent resistance test

[0134] The injection molded article (length 80 mm, width 10 mm, thickness 4 mm) produced in (5) was immersed in a mixed solvent of isooctane / toluene / ethanol = 45 / 45 / 10 mass % at 20°C for 30 days, and changes in appearance were observed and evaluated based on the following criteria.

[0135] A: No abnormalities were observed.

[0136] B: Surface roughness is confirmed.

[0137] (9) Evaluation of film appearance (evaluation of melt formability)

[0138] Using the resin composition pellets obtained in Examples and Comparative Examples, a single-layer film having a thickness of 50 μm was produced under the following film-forming conditions, and the appearance of the obtained film was evaluated based on the following criteria.

[0139] <Single-layer film production conditions>

[0140] Extruder: 20 mm extruder "D2020" manufactured by Toyo Seiki Co., Ltd. (D (mm) = 20, L / D = 20, compression ratio = 3.5, screw: full-screw)

[0141] Cylinder temperature: supply part 190℃, compression part 220℃, metering part 220℃

[0142] Die temperature: 220℃

[0143] Screw speed: 80rpm

[0144] Pulling roller temperature: 40℃

[0145] Film thickness: 50 μm.

[0146] <Evaluation Criteria>

[0147] A: No abnormality was observed on the membrane.

[0148] B: Streaks were observed on the film.

[0149] <Materials used in Examples and Comparative Examples>

[0150] PO(A)

[0151] ·A-1: High-density polyethylene [density 0.95g / cm 3 , MFR (190°C, 2.16kg load) 0.03g / 10min]

[0152] ·A-2: Linear low-density polyethylene [density 0.92g / cm 3 , MFR (190°C, 2.16kg load) 0.03g / 10min]

[0153] EVOH(B)

[0154] B-1: EVOH [ethylene unit content 32 mol%, saponification degree 99.9 mol%, MFR (190°C, 2.16 kg load) 1.6 g / 10 min, density 1.19 g / cm 3 ]

[0155] Acid modified PO(C)

[0156] C1-1: Maleic anhydride grafted modified linear low-density polyethylene [density 0.92g / cm 3 , MFR (measured at 190°C, 2.16 kg load) 1.1 g / 10 min, acid value 1.5 mg KOH / g]

[0157] ·C2-1: Maleic anhydride grafted modified high-density polyethylene [density 0.94g / cm 3 , MFR (measured at 190°C, 2.16 kg load) 25 g / 10 min, acid value 47 mgKOH / g]

[0158] ·C2-2: Maleic anhydride grafted modified high-density polyethylene [density 0.94g / cm 3 , MFR (measured at 190°C, 2.16 kg load) 25 g / 10 min, acid value 15 mg KOH / g]

[0159] Acid modified PO(D)

[0160] D-1: Maleic anhydride grafted modified ethylene-butene copolymer [density 0.87 g / cm 3 , MFR (measured at 190°C, 2.16 kg load) 0.5 g / 10 min, acid value 6 mgKOH / g, glass transition temperature -43°C]

[0161] D-2: Maleic anhydride grafted modified ethylene-butene copolymer [density 0.87 g / cm 3 , MFR (measured at 190°C, 2.16 kg load) 0.5 g / 10 min, acid value 12 mg KOH / g, glass transition temperature -43°C]

[0162] D-3: Maleic anhydride grafted modified ethylene-butene copolymer [density 0.87 g / cm 3 , MFR (measured at 190°C, 2.16 kg load) 0.5 g / 10 min, acid value 27 mgKOH / g, glass transition temperature -43°C]

[0163] D-4: Maleic anhydride grafted modified ethylene-butene copolymer [density 0.86 g / cm 3, MFR (measured at 190°C, 2.16 kg load) 0.5 g / 10 min, acid value 27 mgKOH / g, glass transition temperature -52°C]

[0164] Acid-modified PO (D') used in the comparative example

[0165] ·D'-5: Maleic anhydride grafted modified ethylene-butene copolymer [density 0.885g / cm 3 , MFR (measured at 190°C, 2.16kg load) 5g / 10min, acid value 6mgKOH / g, glass transition temperature -26°C]

[0166] The MFR, glass transition temperature, acid value and density of the above-mentioned material were measured according to the methods described in the above-mentioned evaluation methods (1) to (4).

[0167] <Example 1>

[0168] [Manufacture of recycling aids]

[0169] The acid-modified PO (D-1) was melt-kneaded at 215° C. using a twin-screw extruder (Toyo Seiki Co., Ltd., “2D25W”, diameter 25 mm), and then pelletized using a pelletizer to prepare a recovery aid.

[0170] [Manufacturing of resin composition]

[0171] After dry-blending 2 parts by mass of the obtained recycling aid, 100 parts by mass of PO (A-1), 5 parts by mass of EVOH (B-1), and 10 parts by mass of acid-modified PO (C1-1), the mixture was melt-kneaded using a single-screw extruder ("GT-40-26" manufactured by Plastics Engineering Research Institute, diameter 40 mm) under the following conditions, and pelletized to obtain resin composition pellets.

[0172] <Single screw extruder conditions>

[0173] Extruder: Single screw extruder ("GT-40-26" manufactured by Plastics Engineering Research Institute, diameter 40 mm, L / D = 26)

[0174] Screw speed: 95rpm

[0175] Discharge volume: 20kg / hr

[0176] Cylinder and die temperature setting: C1 / C2 / C3 / C4 / C5 / D = 200℃ / 215℃ / 215℃ / 215℃ / 215℃ / 215℃ Extrusion die: 5 holes

[0177] The obtained resin composition pellets were evaluated for -40°C impact strength, die adhesion, screw adhesion, solvent resistance, and melt moldability according to the methods described in the above evaluation methods (5) to (9). The evaluation results are shown in Table 1.

[0178] <Examples 2 to 12, Comparative Examples 1 to 5>

[0179] A recycling aid and resin composition pellets were prepared and evaluated in the same manner as in Example 1 except that the types of PO (A), EVOH (B), acid-modified PO (C) and acid-modified PO (D) and the amounts of the respective components were changed as described in Table 1. The evaluation results are shown in Table 1. When a plurality of resins were blended in the recycling aid, they were dry-blended in advance and then pelletized under the same conditions as in Example 1 to prepare the recycling aid.

[0180] <Example 13>

[0181] Using PO(A-1), EVOH(B-1) and acid-modified PO(C1-1), three types of five-layer parisons of (inside) PO(A-1) layer / acid-modified PO(C1-1) layer / EVOH(B-1) layer / acid-modified PO(C1-1) layer / PO(A-1) layer (outside) were extruded at 210°C using a blow molding machine "TB-ST-6T" manufactured by Suzuki Industries, and blow-molded in a mold at 15°C. The mixture was cooled for 20 seconds to form a 500ml container with a total layer thickness of 3450μm [(inside) PO(A-1) layer / acid-modified PO(C1-1) layer / EVOH(B-1) layer / acid-modified PO(C1-1) layer / PO(A-1) layer (outside) = 1500 / 150 / 150 / 150 / 150]. The obtained container was pulverized, and 2 parts by mass of the recovery aid (acid-modified PO (D-1) particles) produced in Example 1 were added to 115 parts by mass of the obtained pulverized product, and resin composition particles were produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0182] <Example 14>

[0183] Resin composition pellets were produced and evaluated in the same manner as in Example 13 except that 2 parts by mass of the recycling aid produced in Example 5 were added instead of the recycling aid produced in Example 1. The results are shown in Table 1.

[0184]

Claims

1. A resin composition for food packaging containers and fuel containers, wherein: The present invention comprises 0.1 to 20 parts by mass of an ethylene-vinyl alcohol copolymer (B), 0.1 to 20 parts by mass of an acid-modified polyolefin (C), and 0.1 to 10 parts by mass of an acid-modified polyolefin (D) relative to 100 parts by mass of the polyolefin (A). The ethylene unit content of the ethylene-vinyl alcohol copolymer (B) is 15 to 60 mol% and the saponification degree is 85 mol% or more. The density of polyolefin (A) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 , The density of the acid-modified polyolefin (C) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 , The density of the acid-modified polyolefin (D) is 0.85 g / cm 3 Above and less than 0.88g / cm 3 The glass transition temperature measured by dynamic viscoelasticity measurement is -30°C or less.

2. The resin composition according to claim 1, wherein The acid value of the acid-modified polyolefin (D) is 3 mgKOH / g or more and less than 100 mgKOH / g.

3. The resin composition according to claim 1 or 2, wherein The acid-modified polyolefin (C) includes an acid-modified polyolefin (C1) having an acid value of 0.1 mgKOH / g or more and less than 10 mgKOH / g and an acid-modified polyolefin (C2) having an acid value of 10 mgKOH / g or more and less than 100 mgKOH / g.

4. The method for producing a resin composition according to claim 3, wherein include: A step of melt-kneading a recycled product of a multilayer structure comprising a polyolefin (A) layer, an ethylene-vinyl alcohol copolymer (B) layer and an acid-modified polyolefin (C1) layer, and a recycling aid comprising an acid-modified polyolefin (C2) and an acid-modified polyolefin (D). 5 . A multilayer structure comprising a layer containing the resin composition according to claim 1 as a main component.

6. The multilayer structure according to claim 5, wherein The film further comprises a polyolefin (A) layer, an ethylene-vinyl alcohol copolymer (B) layer, and an acid-modified polyolefin (C1) layer.

7. A molded article using the multilayer structure according to claim 5 or 6.

8. A fuel container using the multilayer structure according to claim 5 or 6.

9. Recovery aids, including: Contains an acid-modified polyolefin (D) and an acid-modified polyolefin (C2), wherein the density of the acid-modified polyolefin (D) is 0.85 g / cm 3 Above and less than 0.88g / cm 3 , and the glass transition temperature measured by dynamic viscoelasticity measurement is -30°C or less, The mass ratio C2 / D of the acid-modified polyolefin (C2) to the acid-modified polyolefin (D) in the recovery aid is 10 / 90 to 90 / 10, The proportion of the acid-modified polyolefin (D) and the acid-modified polyolefin (C2) in the recycling aid is 90% by mass or more, and the density of the acid-modified polyolefin (C2) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 , the acid value is greater than 10 mgKOH / g and less than 100 mgKOH / g.

10. The recycling aid according to claim 9, further comprising a polyolefin (A), The mass ratio A / D of the polyolefin (A) to the acid-modified polyolefin (D) in the recovery aid is 10 / 90 to 90 / 10, The proportion of the acid-modified polyolefin (D), the acid-modified polyolefin (C2) and the polyolefin (A) in the recycling aid is 90% by mass or more, The density of the polyolefin (A) is 0.89 g / cm 3 Above and less than 0.97g / cm 3 .

11. The recovery aid according to claim 9 or 10, wherein: The acid value of the acid-modified polyolefin (D) is 3 mgKOH / g or more and less than 100 mgKOH / g.

12. The recovery aid according to claim 9 or 10, wherein: Contains a density of 0.91g / cm 3 Above 0.94g / cm 3 The acid-modified polyolefin (C2) has an acid value of 12 mgKOH / g or more and 80 mgKOH / g or less, and the mass ratio C2 / D of the acid-modified polyolefin (C2) to the acid-modified polyolefin (D) is 10 / 90 to 90 / 10.

13. The recovery aid according to claim 10, wherein: Contains a density of 0.94g / cm 3 Above 0.96g / cm 3 In the following polyolefin (A), the mass ratio A / D of the polyolefin (A) to the acid-modified polyolefin (D) is 10 / 90 to 90 / 10.

Citation Information

Patent Citations

  • Mixed resin and multilayer structure

    WO2012060371A1

  • Resin composition, method for producing same and multi-layered structure using same

    WO2019021996A1

  • Resin composition, method for producing same and multi-layered structure using same

    CN109642058A

  • Resin component for producing automobile exterior part

    JP2006022131A